MILITARY MEDIATION AS A NEW FORM OF NEGOTIATION PROCESS - Sliusarenko, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . In today’s world, where the number of armed conflicts continues to rise, the issue of their resolution is becoming increasingly urgent. According to the international online platform Rule of Law in Armed Conflicts (RULAC), there are currently over 110 armed conflicts worldwide involving at least 55 states and more than 70 non-state armed actors. Military mediation is an emerging branch of negotiation aimed at resolving conflicts within the military domain. The use of military mediation enables de-escalation of violence and contributes to the achievement of peace agreements. This article explores the concept of military mediation, its key characteristics, methods, and effectiveness under contemporary conditions. M e t h o d s . he study is based on the application of the following scientific methods: Literature analysis – the theoretical foundations of military mediation and its implementation in international conflict resolution; Comparative method – juxtaposition of various approaches to armed conflict resolution through mediation; Modelling method – development of potential scenarios for applying military mediation in current conflicts; Empirical method – analysis of real-world cases of successful implementation of military mediation in the history of international relations. R e s u l t s . The research summarises and systematises data concerning: the classification of armed conflicts and their impact on international security; methods of negotiation within the military domain and their specific features; the use of military mediation in conflict resolution; international experience in the application of military mediation across various countries; practical aspects of military mediation, its effectiveness, and prospects for development. C o n c l u s i o n s . Military mediation is an effective tool for preventing the escalation of armed conflicts, allowing for the achievement of compromises and the signing of peace agreements. It holds significant potential for conflict resolution both at the international and national levels. The core principles of military mediation include neutrality, confidentiality, flexibility, and adherence to international humanitarian law. Notable examples of military mediation include the peace process in Colombia, negotiations in Libya, Sudan, Cyprus, and others. The successful application of military mediation requires the development of professional training programmes for military mediators and the implementation of new approaches to peaceful conflict resolution.